An Open-Label Comparison of Local Anesthesia with or without Sedation for Minor Hand Surgery. (December 2014) - Rozanski, Marta; Neuhaus, Valentin; Reddy, Rajesh; Jupiter, Jesse B.; Rathmell, James P.; Ring, David C.
Background: The purpose of this study was to assess satisfaction and pain intensity in patients undergoing minor hand surgery under local anesthesia (LA) with or without sedation. Methods: Seventy-three adult patients presenting to two hand surgeons were enrolled in this prospective observational study in 2012. They completed questionnaires prior to surgery (current pain intensity, Patient Health Questionnaire-2 (PHQ-2) to measure symptoms of depression, Pain Self-Efficacy Questionnaire (PSEQ) to assess the effective coping strategy of pain self-efficacy) and within 48 h after surgery (satisfaction with surgery, satisfaction with anesthesia, pain during the injection, and pain during the procedure). Thirty-seven patients had carpal tunnel release (bilateral in 3), 22 had release of one or more trigger digits, and 12 had excision of a benign tumor, gouty tophus (1 patient), or foreign body (1 patient). Forty-six patients chose LA and 27 chose LA with sedation. Results: There was no difference in satisfaction with surgery or anesthesia by the type of anesthesia. Satisfaction with surgery was associated with older age alone. Satisfaction with anesthesia was associated with no prior surgery for the same condition. Pain during injection and during the procedure were significantly higher without sedation. Pain during injection was associated with younger age and LA. No factors were associated with pain during the procedure. Conclusions: Patients that had local anesthesia immediately prior to incision with tourniquet use during surgery had more pain during the procedure but were equally satisfied on average with surgery and with anesthesia compared to patients that had sedation.